Petronas Carigali Sdn. Bhd., Sarawak Operations / Haziah Malim Sidik Malim and Jahranah Sallih Udin - Sallih Udin, Jahranah; Sidik Malim, Haziah Malim (2023)
PETRONAS, short for Petroliam Nasional Bhd, is Malaysia's national petroleum corporation established on 17 August 1974. Petronas Carigali Sdn Bhd (PCSB) is a subsidiary of Petroliam Nasional Berhad (PETRONAS). It operates in domestic and international and Sarawak Operations (SKO) is one of its domestic operations. PETRONAS eLearning Solutions Sdn Bhd (PeLSSB) is another subsidiary of PETRONAS with MSC Status, to handle the execution and deployment of eLearning to ensure focus and cohesiveness for the eLearning program.